Analisis Pengaruh Kompensasi dan Motivasi terhadap Kinerja Karyawan PT Kokapura Avia di Bandar Udara Internasional Yogyakarta Kulon Progo - Fauziah, Syifa; Siahaan, Shintia Marinda (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Human Resources are very important for companies in organizing, managing, and utilizing its employees, so that they can function productively in order to achieve the company's goals. To achieve the goals of a company, it is necessary to have human resources who have good and satisfactory performance. Compensation and motivation are included in the factors that influence employee performance. If the provision of compensation and motivation provided by the company to its employees is good and in accordance with the needs, then the increase in employee performance will also be good. The existence of this study aims to determine the effect of compensation and motivation on the performance of employees of PT. Kokapura Avia at Yogyakarta International Airport. This study uses a quantitative approach. Samples taken at PT. Kokapura Avia at Yogyakarta International Airport, namely 84 respondents who were surveyed in this quantitative study. Data collection is done by giving questionnaires to employees. The results showed that compensation affects the performance of employees at PT. Kokapura Avia at Yogyakarta International airport. This is evidenced by the results of the t_hitung value of 3.234 ˃ t_tabel 1.663 360 with a significant level of 0.002 <0.05. And the variable motivation affects the performance of employees of PT. Kokapura Avia with a proven value of a significant level of 0.008 <0.05 and a t_hitung value of 2.737 ˃ t_tabel 1.663. The influence of the Compensation and Motivation variables together on the Employee Performance variable has a positive and significant influence by having an Adjusted R square value of 0.534 which means 53.4%.Differences in motivational indicators make the Adjusted R square value in this study smaller than previous studies. Keywords: Compensation, Motivation, Employee Performance